Characterization of NCS1–InsP3R1 interaction and its functional significance - Nguyen, Lien D. (J Biol Chem, 2019)
Inositol 1,4,5-trisphosphate receptors (InsP3Rs) are endoplasmic reticulum–localized channels that mediate Ca(2+) release from the endoplasmic reticulum into the cytoplasm. We previously reported that an EF-hand Ca(2+)-binding protein, neuronal calcium sensor 1 (NCS1), binds to the InsP3R and thereby increases channel open probability, an event associated with chemotherapy-induced peripheral neuropathy. However, the exact NCS1-binding site on InsP3R remains unknown. Using protein docking, co-immunoprecipitation, and blocking peptides, we mapped the NCS1-binding site to residues 66–110 on the suppressor domain of InsP3R type 1 (InsP3R1). We also identified Leu-89, a residue in the hydrophobic pocket of NCS1, as being critical for facilitating the NCS1–InsP3R1 interaction. Overexpression of WT NCS1 in MDA-MB231 breast cancer cells increased Ca(2+) signaling and survival, whereas overexpression of Leu-89 NCS1 variants decreased Ca(2+) signaling and survival, further suggesting the importance of this residue in the NCS1–InsP3R1 interaction. In conclusion, we show that NCS1–InsP3R1 interaction enhances intracellular Ca(2+) signaling in cells and can be modulated by altering or occluding the hydrophobic pocket of NCS1. This improved understanding of the NCS1–InsP3R1 interaction may facilitate the development of management strategies for diseases resulting from aberrant NCS1 expression.